Preference for breeding goal traits among Swedish and Norwegian dairy farmers - Skjerve, Torgunn Aslaug (2017)
The aim of this study was to investigate similarities and differences among Norwegian and Swedish dairy farmers’ preference for breeding goal traits, and compare systematic effects within each country. The specific objectives were to analyse variation in ranking among farmers, and derivate relevant clusters using cluster analysis. Further objectives were to identify similarities and differences in farm and farmer characteristics between clusters, and compare these between the two countries. Data of ranking of 15 traits, and information about the respondents and their herd, was collected in a questionnaire sent out to Swedish (2012) and Norwegian (2017) dairy farmers. Rankings were analysed using cluster analysis and Friedman test. The Swedish respondents ranked longevity highest, followed by a high-ranked group of four traits; fertility, milk production, mastitis resistance and leg and hoof health. A group of moderately ranked traits included calving difficulties, feed conversion, disease resistance, temperament, lactation curve and roughage intake, where calving difficulties was significantly higher ranked than lactation curve and roughage intake. Carcass classification, meat production and parasite resistance formed a low-ranked group, but methane production had the lowest ranking. Norwegian respondents ranked fertility highest, followed by a high-ranked group of four traits; milk production, temperament, longevity and leg and hoof health, however ranking of leg and hoof health, mastitis resistance, roughage intake and calving difficulties was ranked higher than feed conversion and disease resistance in the group of moderately ranked traits. Meat production and carcass classification was the highest ranked of the low-ranked traits. As for the Swedish respondents, the Norwegian respondents also ranked methane production the lowest. Three clusters were derived from the Swedish respondents’ ranking of traits: “Milk production and Efficiency” (ME), “Robustness” and “Milk production and robustness” (MR). From the Norwegian questionnaire, four clusters were derived: “Milk production, meat production and functionality” (MMF), “Fertility and efficiency” (FE), “Robustness and Health” (RH) and “Milk production and health” (MH). In both Sweden and Norway respondents in two of the clusters ranked milk production the highest, of which the cluster MR in Sweden and the cluster MMF in Norway were the larger. Respondents in these cluster had a higher ranking of temperament, while respondents in the Norwegian cluster MH and the Swedish cluster MR had a higher ranking of health traits. The two clusters with the largest number of respondents in both Sweden and Norway had either a high or a medium-high ranking of milk production. In Sweden the cluster ME, where respondents gave the highest rank to milk production, was the largest, followed by the Robustness cluster. In Norway the cluster FE, where respondents ranked milk production medium-high was the largest, followed by the MMF cluster. Some differences were found both for production-, herd- and farm-related characteristics of respondents between clusters, but many did not seem to affect cluster designation. The results of this study suggest a broad variation in dairy farmer’s preference for breeding goal traits in Norway and Sweden, affected both by the current status of the herd, production system and personal values. However, the reasoning behind farmers’ ranking is unclear, and further studies on the gathered data is needed to get a fuller picture.